IMPLEMENTASI PROGRAM MERDEKA BELAJAR KAMPUS MERDEKA - Neng Virly Apriliyani; Denny Hernawan; Irma Purnamasari; Gotfridus Goris Seran; Berry Sastrawan (LPPM Universitas Djuanda Bogor, 2022)
The aim of this research is to find out the impact of implementation of Freedom to Learn Independent Campus Program (MBKM Program) on the Study Program of Public Administration. The main aim of MBKM Program is basically intended to give freedom for higher education institutions to be more autonomous, independent, less bureaucratic, and innovative in producing highly qualified graduates. To achieve the main aim, the implementation of MBKM Program includes eight learning activities, namely student exchange, internship/work practice, teaching assistant in the education unit, research, humanitarian project, entrepreneurship, independent study/project, and thematic field work. The Study Program of Public Administration has implemented two learning activities, namely student exchange and internship/work practice. Results of this research indicate that the implementation of MBKM Program impacts on some aspects, namely improvement of experiential learning to build hard and soft skills of students, fulfilment of learning achievement of graduate, and improvement of lecturer capacity. Moreover, this research identifies the presence of constraints on the implementation of MBKM Program in the cases of curriculum revision, redesign of academic information system, and fund problem for student.